In-Situ Messung von Halogenoxiden in der polaren Stratosphäre: Untersuchungen zur Ozonchemie im Winter 1994/95 - Woyke, T. (Forschungszentrum Jülich, Zentralbibliothek, Verlag, 1998)
The aim of this thesis is the investigation of chemical ozone loss processes in the Arctic winter stratosphere. Within the framework of the Second European Stratospheric Arctic and Midlatitude Experiment (SESAME) the Jülich Research Center in cooperation with the University of California at Irvine performed on 3 February 1995 balloon borne in-situ measurements in the Arctic polar vortex using a combined payload, which allowed for the simultaneous observation of long-lived trace gases, chlorine containing source gases, ozone and the halogen radicals CIO and BrO, which participate in catalytic cycles leading to ozone loss. Between 19-23 km a layer of enhanced CIO mixing ratios with maximum values of 1150 pptv was observed with BrO mixing ratios of X10 pptv nearly independent of altitude. The observations show for the first time an anticorrelation between CIO and O$_{3}$ in the Arctic polar vortex, similar to the one observed over Antarctica as early as 1987, which was a key evidence in linking halogen oxides with ozone loss. The data set obtained during the balloon flight is analyzed with regard to the following aspects. The observed enhanced CIO/Cl$_{y}$ ratio of 0.4 in this layer compared to 0.05 typical for out-of-vortex conditions indicates chlorine activation in the Arctic polar vortex in the winter 1994/95. This view is supported by HCl measurements made by the HALOE satellite instrument inside the Arctic polar vortex indicating a near complete loss of the chlorine reservoir species HCl. Applying the method of tracer correlations a chemical ozone loss of 1±0.3 ppmv (~30 %) for the early winter period until the day of the measurement is derived for the altitudes around 21 km (480 K potential temperature), which can be confirmed by independent methods. A quantitative comparison of simulated ozone loss using a chemical box model with the derived ozone loss shows, that the model underestimates the early winter ozone loss approximately by a factor of two, although the profile observations of HCl and CIO are well ...